Propuesta de mejora del sistema de secado de producto granulado empleado en la empresa Punto Natural Zamora Prieto S.A.S. (2017)
This project was developed in Punto Natural Zamora Prieto S.A.S Company, where it was proposed to improve the drying system of granulated product, through the basic conception of a batch dryer of vacuum trays. For this was necessary in the diagnostic principle the drying system currently used in the company for the dehydration of the granulated product, in order to establish which were the failures involved in the drying process and on the installed equipment. For the diagnosis a detailed description of the drying process was made, specifying drying times, operational conditions, modes of dryer operation, powers and capacities of each dryer component and subsystems. In addition, a brief description of the product's production process was carried out, in order to determine the causes involved in the excessive drying time of the product by analyzing the causes of the drying process. Based on the analysis described, it was proposed the design of a new drying equipment based on the demand established by the company, additionally proposes actions on the current system that allows to improve the existing drying behavior.